2013
DOI: 10.1093/brain/awt236
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing for molecular diagnosis of neurological disorders using ataxias as a model

Abstract: Many neurological conditions are caused by immensely heterogeneous gene mutations. The diagnostic process is often long and complex with most patients undergoing multiple invasive and costly investigations without ever reaching a conclusive molecular diagnosis. The advent of massively parallel, next-generation sequencing promises to revolutionize genetic testing and shorten the ‘diagnostic odyssey’ for many of these patients. We performed a pilot study using heterogeneous ataxias as a model neurogenetic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
139
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 62 publications
12
139
4
Order By: Relevance
“…A third advantage of gene panels is largely avoiding the detection of incidental findings, which have been discussed above. Gene panels have been developed for, and are being applied to, many neurological disorders, including epilepsy [11], ataxia [54], and dementia [55].…”
Section: Diagnostic Settingmentioning
confidence: 99%
“…A third advantage of gene panels is largely avoiding the detection of incidental findings, which have been discussed above. Gene panels have been developed for, and are being applied to, many neurological disorders, including epilepsy [11], ataxia [54], and dementia [55].…”
Section: Diagnostic Settingmentioning
confidence: 99%
“…Németh et al [22] demonstrated the utility of this approach by using next generation sequencing in an attempt to determine the underlying mutations in 50 patients with familial or earlyonset ataxia who had previously been tested for SCA types 1, 2, 3, 6, 7 and FRDA. Targeted capture performed on 117 candidate genes revealed 13 pathogenic mutations (nine of which were novel) in the patient cohort, indicating that the inclusion of this strategy may be advantageous in diagnostic laboratories.…”
Section: The Futurementioning
confidence: 99%
“…NGS determined that DARS2 is also mutated in ataxia and spasticity [78]. Genome scan has shown that DARS2 is associated with T2DM [79]. T2DM has association with many other ARS2 genes.…”
Section: Ars/ars2 Gene Mutation Causing Diseasesmentioning
confidence: 99%
“…Leucyl tRNA synthetase, LARS2, and threonyl tRNA synthetase, TARS2 are susceptibility genes of T2DM. H324Q variant of LARS2 is thought to enhance T2DM [78,79]. Premature ovarian failures accompanied by hearing loss symptoms compose Perrault Syndrome.…”
Section: Ars/ars2 Gene Mutation Causing Diseasesmentioning
confidence: 99%